Spatio-Temporal Translations: Practices of Intimacy under Absence. Issue 1 (1st March 2021) - Baffelli, Erica; Schröer, Frederik
Abstract: During the COVID-19 pandemic, access to space has been strictly regulated and restricted. Many of us feel acutely disconnected from our relationships, while at the same time new forms of (virtual) intimacies have become ubiquitous. In the pandemic present, nearly all interpersonal relations are now characterised by a double absence that is concrete and material, and also emotional and felt. This article offers a theoretical reflection on how conditions of absence create new practices of intimacy and new strategies of coping. It does so by discussing how pre-pandemic emotional repertoires are translated into new forms of intimacy that can synchronise or throw out of sync. It highlights the centrality of spatial and temporal relations under absence in uncovering new mediated practices.